2015
DOI: 10.1128/jcm.02182-15
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Xpert MTB/RIF Assay in Diagnosis of Pleural Tuberculosis by Use of Pleural Fluid Samples

Abstract: Prospectively, 162 pleural fluid samples from patients with probable tuberculous pleural effusion were tested by the Xpert MTB/ RIF assay and the Bactec MGIT-960 culture system. Of these, 43 (26.5%) were positive in the MGIT-960 culture, and 23 (14.2%), in the Xpert MTB/RIF assay. The sensitivity and specificity of the Xpert MTB/RIF compared with the MGIT-960 culture were 54.8% and 100%, respectively. T uberculosis (TB) affects one third of the global population in developing countries, with annual estimates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 15 publications
(20 reference statements)
4
25
1
1
Order By: Relevance
“…There was no rifampicin resistance in the population studied, all the 23 MTB positive samples detected by Gene Xpert-MTB/RIF assay in our study were sensitive to Rifampicin. This finding was in accordance with Rufai et al [14], who have also reported similar sensitivity of rifampicin, whereas Pravin et al [11] detected Rifampicin resistance in 4 out of 16 MTB detected in the pleural fluid and one rifampicin resistance out of 5 MTB detected in the ascitic fluid samples.…”
Section: Original Research Articlesupporting
confidence: 90%
See 1 more Smart Citation
“…There was no rifampicin resistance in the population studied, all the 23 MTB positive samples detected by Gene Xpert-MTB/RIF assay in our study were sensitive to Rifampicin. This finding was in accordance with Rufai et al [14], who have also reported similar sensitivity of rifampicin, whereas Pravin et al [11] detected Rifampicin resistance in 4 out of 16 MTB detected in the pleural fluid and one rifampicin resistance out of 5 MTB detected in the ascitic fluid samples.…”
Section: Original Research Articlesupporting
confidence: 90%
“…In a study conducted by Praveen et al [11], they found 10.1% plueral fluid sample positive for MTB by Gene Xpert and Hillemann et al [13] found 3 positive GeneXpert results out of 113 pleural fluid samples (2.9%) all of which were negative on mycobacterial culture, the positivity rate for pleural fluids in our study was 6.06% (8/132) was in accordance with above studies. Rufai et al [14] showed that the Xpert has very low diagnostic sensitivity of 14.2% in pleural fluid, even in culture proven cases. Porcel et al [15] concluded that the Xpert MTB/RIF assay has a limited diagnostic capacity for pleural fluid samples of TB origin.…”
Section: Discussionmentioning
confidence: 99%
“…[30] However, its sensitivity for diagnosing TB pleurisy is disappointingly low. [31][32][33][34] Recently, a meta-analysis reported the pooled sensitivity and specificity of Xpert MTB/RIF to be 37% and 92%, respectively, in TB pleurisy. [35] The paucibacillary nature of pleural specimens was considered to be the main reason for this.…”
Section: Infectious Diseasesmentioning
confidence: 99%
“…The definite diagnosis of TP is made by detecting Mycobacterium tuberculosis from the pleural effusion (PE), sputum, or pleural tissue (1,2). However, due to the paucity of M. tuberculosis organisms in PE, culture and molecular tests like the Xpert MTB/RIF assay show poor sensitivities (3)(4)(5).…”
mentioning
confidence: 99%